Identification and characterization of a purple nonsulfur bacterium isolated from coastal area of Hai Phong for using in production of unsaturated fatty acid (omega 6, 7, 9) - Yen, Hoang Thi; Quynh, Tran Thi Thu; Ha, Chu Hoang; Tuyen, Do Thi; Thanh, Dang Tat; Hang, Dinh Thi Thu (Vietnam Journal of Science and Technology, 2019)
Purple nonsulfur bacteria are a group that has so much biotechnological applications, particularly in producing of functional food rich with unsaturated fatty acids. A purple nonsulfur bacterium (named HPB.6) was chosen based on its strong growth, high lipid and synthesis of unsaturated fatty acid (omega 6,7,9). Studying on basic biological characteristics showed that the cells of HPB.6 were observed as ovoid-rod shape, none motility, Gram negative staining. The diameter of single bacterium was about 0.8-1.0 µm. The cells divide by binary fission and had bacteriochlorophyll a (Bchl a). This bacterium grew well on medium with carbon and nitrogen sources such as acetate, succinate, pyruvate, butyrate, glutamate, arginine, leucine, tyrosine, alanine, methionine, threonine, glutamine, yeast extract and NH4Cl. This selected strain grew well on medium with salt concentrations from 1.5 - 6.0% (optimum 3%), pH from 5.0 to 8.0 (optimum at pH 6.5) and could withstand Na2S at 4.0 - 5.2 mM. Based on morphological, physiological properties and 16S rRNA analysis received demonstrated that HPB.6 strain belongs to the species Rhodovulum sulfidophilum.